Susceptibility and resistance mechanisms to insecticides in Bactericera cockerelli (Sulc.) in Coahuila, Mexico - Dávila Medina, Miriam Desireé; Cerna Chávez, Ernesto; Aguirre Uribe, Luis Alberto; García Martínez, Oswaldo; Ochoa Fuentes, Yisa María; Gallegos Morales, Gabriel; Landeros Flores, Jerónimo (Revista Mexicana de Ciencias Agrícolas, 2018)
Bactericera cockerelli (Sulc.) causes significant losses in potato (Solanum tuberosum L.) in northeastern Mexico. Its control is based on the application of insecticides, but producers perceive that its control is unsatisfactory and an increased number of applications. Therefore, the objective of this research was to determine the level of susceptibility and resistance metabolic mechanisms involved, by evaluating the following insecticides Cyalotrina, deltamethrin, imidacloprid, Omethoate, Dimethoate, Malathion, Endosulfan, Carbofuran, Methomyl, Primicarb and Spinosad alone and in combination with the synergists diethyl maleate (DEM); SSS- tributylphosphorotrithoate (DEF) and piperonyl butoxide (PB). To do this, adults were collected from B. cockerelli on potato producing areas of the state of Coahuila, to conduce the bioassays, it was used the leaf immersion method proposed by the Action Committee Insecticide Resistance IRAC (for its acronym in English). It was found that the lowest LC50 for B. cockerelli presented by the products Deltamethrin, Endosulfan, Pirimicarb and Spinosad (31.2, 149.31, 155.79 and 156.64 ppm respectively). In the mixture of the insecticide synergists, the highest values of synergism were obtained with DEF, indicating the esterases enzymes are the metabolic mechanism of resistance with a greater presence for the study population.
Keywords: co toxicity coefficient; enzymatic resistanc; psyllid